Transnasal endoscopy: moving from endoscopy to the clinical outpatient–blue sky thinking in oesophageal testing. Issue Volume 13:Issue e1(2022) (31st May 2022) - Lim, Samuel; Haboubi, Hasan Nadim; Anderson, Simon H C; Dawson, Patrick; Machado, Ana Paula; Mangsat, Edna; Santos, Sara; Wong, Terry; Zeki, Sebastian; Dunn, Jason
Abstract : Background: COVID-19 has severely affected UK endoscopy services with an estimate 86% loss of activity during the first wave. Subsequent delays in diagnostic and surveillance procedures highlight the need for novel solutions to tackle the resultant backlog. Transnasal endoscopy (TNE) provides an attractive option compared with conventional upper gastrointestinal endoscopy given its limited use of space, no sedation and reduced nursing resources. Our experience: We describe piloting and then establishing an outpatient model TNE service in the pandemic era and the implications on resource allocation, training and workforce. We also discuss our experiences and outline ways in which services can evolve to undertake more complex endoscopic diagnostic and therapeutic work. Over 90% of patients describe no discomfort and those who have previously experienced conventional transoral endoscopy preferred the transnasal approach. We describe a low complication rate (0.8%) comprising two episodes of mild epistaxis. The average procedure duration was reasonable (9.9±5.0 min) with full adherence to Joint Advisory Group quality standards. All biopsies assessed were deemed sufficient for diagnosis including those for surveillance procedures. Discussion: TNE can offer a safe, tolerable, high-quality service outside of a conventional endoscopy setting. Expanding procedural capacity without impacting on the current endoscopy footprint has great potential in recovering endoscopy services following the COVID-19 pandemic. Looking forward, TNE has potential to be used both within the endoscopy suite as part of therapeutic procedures, or outside of the endoscopy unit in outpatient clinics, community hospitals, or mobile units and to achieve this in a more sustainable and environmentally friendly way.